Analisis Roland Barthes Pada Poster Iklan Belanja Shopee dan Ramayana Edisi Lebaran Ceria - Fardilla Dwi Utami (AL-IDZA'AH: Jurnal Dakwah dan Komunikasi, 2021)
Mass media can anesthetize the audience, not only presenting written content, information, education or entertainment, but advertising is an attraction that cannot be ignored. We have actually felt the potential of advertising through electronic mass media. How not, advertisements that serve everyday foods and drinks with certain brands can turn into one of the favorite menus with store branches everywhere. The people of Indonesia have extraordinary shopping potential, as it is approaching Eid al-Fitr. Some advertisements become an attraction for hunting for clothes, food and all knick-knacks on the day of victory. The Ramayana advertisement poster together with an online shopping shop Shopee is one of the reasons the author examines the digital potential of mass media with Muslim culture. This study uses a semiotic research style with Roland Barthes' theoretical approach to explore the facts, signs, and myths implied in advertising posters. In addition, the author tries to explore cultural approach of Indonesia Muslims in welcoming Eid by using new clothes for cultural activities that have become hereditary tradition.